2008
DOI: 10.1111/j.1365-2990.2007.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β‐amyloid peptide on the density of M2 muscarinic acetylcholine receptor protein in the hippocampus of the rat: relationship with GABA‐, calcium‐binding protein and somatostatin‐containing cells

Abstract: Our findings suggest that A beta induces a significant reduction in M2mAChR-immunoreactivity in the CA1 of the hippocampus and a reduction in GABAergic interneurones containing M2mAChR, which may contribute to impairment of GABAergic synaptic transmission in area CA1 of hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Physiological studies revealed that persistent plasticity, such as long‐term potentiation and long‐term depression, occurred in the cortex of the tree shrew and that the cholinergic system was involved in that plasticity [43]. The cholinergic system is a key to Alzheimer’s disease [10, 61], and the degeneration of SS and the formation of plaques are involved in Aß and Alzheimer’s disease as discussed earlier [12, 19, 40]. Tree shrews are suitable model animals for studying cognitive function and age‐related changes.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies revealed that persistent plasticity, such as long‐term potentiation and long‐term depression, occurred in the cortex of the tree shrew and that the cholinergic system was involved in that plasticity [43]. The cholinergic system is a key to Alzheimer’s disease [10, 61], and the degeneration of SS and the formation of plaques are involved in Aß and Alzheimer’s disease as discussed earlier [12, 19, 40]. Tree shrews are suitable model animals for studying cognitive function and age‐related changes.…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting association with hippocampal pathology (Fig. 6) could potentially implicate disruptions of vulnerable direct inhibitory hippocampal projections (González et al, 2008; Jinno et al, 2007; Miyashita and Rockland, 2007; Perez et al, 2010), opposite to excitatory anterior thalamic input (Gonzalo-Ruiz et al, 1997; Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further supported by evidence of pathology at prodromal stages in those pathways that project to the retrosplenial cortex (Fellgiebel et al, 2008; Xie et al, 2006; Zhang et al, 2007; Zhou et al, 2008). Dysfunction in turn may spread throughout the network, as suggested by the demonstrations that infusions of amyloid species into the retrosplenial cortex can have downstream effects (Arevalo-Serrano et al, 2008; González et al, 2008; González et al, 2007; Gonzalo-Ruiz and Arévalo-Serrano, 2006; Gonzalo-Ruiz and Sanz, 2002; Perez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The densitometric analysis was performed according to the general procedure described by Gonzalez et al (2008). Color images of the immunohistological material were captured with a kappa DX 40 camera connected to a Zeiss Axioplan 2 microscope and to a PC computer.…”
Section: Methodsmentioning
confidence: 99%